2014
DOI: 10.1016/j.jstrokecerebrovasdis.2013.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Negative Stroke: Diagnoses and Outcomes in Intravenous Tissue Plasminogen Activator–Treated Patients

Abstract: Background/Purpose Intravenous Alteplase (t-PA) improves outcome in patients with acute ischemic stroke. Of those with full recovery, some may not have had ischemia. We analyzed the frequency and post-treatment outcomes of stroke code patients with no imaging evidence of stroke in order to establish the incidence of neuroimaging negative cerebral ischemia (NNCI) and stroke mimics treated with t-PA. In addition, we compared these patients to the group of stroke patients with imaging evidence of acute stroke to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
(13 reference statements)
0
10
0
1
Order By: Relevance
“…We report the safe use of tPA in 10 HIV patients who did not have ischemic strokes. Although other studies have reported the safe administration of IV-tPA to patients with stroke mimics,(5,6) we extend this finding to the population with potential CNS OIs. Although efficacy data were not available for the entire cohort, there was a clinically significant reduction in NIHSS score post-thrombolysis (decrement from 9 to 4 on average).…”
Section: Discussionmentioning
confidence: 55%
“…We report the safe use of tPA in 10 HIV patients who did not have ischemic strokes. Although other studies have reported the safe administration of IV-tPA to patients with stroke mimics,(5,6) we extend this finding to the population with potential CNS OIs. Although efficacy data were not available for the entire cohort, there was a clinically significant reduction in NIHSS score post-thrombolysis (decrement from 9 to 4 on average).…”
Section: Discussionmentioning
confidence: 55%
“…Negative neuroimaging for cerebral ischemia is common post thrombolysis. In well characterised thrombolysis cohorts, approximately 20% of post-thrombolysis patients [27,28] had no evidence of ischemia on follow up neuroimaging. We reported 31 (12.1%) patients with negative neuroimaging in our cohort, which is lower than published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Giving a treatment with a historical 6.4% symptomatic hemorrhage in the treatment arm of the landmark study 12 seems risky when the assumed outcome of the patient in question is spontaneous recovery. It is notable that mild strokes were largely excluded from the NINDS trials 13 , and that many studies 19 - 21 have since demonstrated safety of treatment of TIAs and stroke mimics with rtPA. Our data shows a likely lower risk of ICH in our treated mild cohort, but only a prospective study comparing treated versus non-treated patients can confirm these results.…”
Section: Discussionmentioning
confidence: 99%